Watershed Rehabilitation in the River Valley Projects: some Aspects - Das, B.L. (Journal of Soil and Water Conservation, 2022)
Rehabilitation of Watersheds has assumed considerable importance in Orissa, due to the construction of two major river valley Projects namely the Hirakud and the Machkund Projects. The Forest Department and the Soil Conservation Organisation of the State Government are now actively engaged in this work. Recently several afforestation Divisions have been created to tackle the denuded hill slopes in the catchment areas of the above two Projects. The object of all these is not only to lengthen the life periods of different reservoirs, but also to strengthen the effectiveness of their operation. Some aspects of Watershed behaviour and their problem of rehabilitation have been discussed in this article.